Psychological Themes in Classical Islamic Literature: A Primary Source Reader - Keshavarzi, Hooman (Brill Academic Publishers, 2025)
This book provides a window into the Islamic scholarly tradition as it relates specifically to the subject of human psychology. It brings together selected segments from the Islamic scholarly literature that address key questions in the field of psychology. These include the admissibility and validity of diverse sources of knowledge, the nature of the human psyche and human drives, the mind and body problem, nature versus nurture, dreams, emotions, psychologic